2022
DOI: 10.1186/s13014-022-02172-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-based DVH estimation and optimization for breast VMAT plans with and without avoidance sectors

Abstract: Background To analyze RapidPlan knowledge-based models for DVH estimation of organs at risk from breast cancer VMAT plans presenting arc sectors en-face to the breast with zero dose rate, feature imposed during the optimization phase (avoidance sectors AS). Methods CT datasets of twenty left breast patients in deep-inspiration breath-hold were selected. Two VMAT plans, PartArc and AvoidArc, were manually generated with double arcs from ~ 300 to ~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The dose distribution predicted by the model for the IMRT plan was comparable to the dose distribution expected for an IMRT plan with 178 small fields. Therefore, the technique of using the VMAT model to predict IMRT plans does not impose any limitations on the dose distribution [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose distribution predicted by the model for the IMRT plan was comparable to the dose distribution expected for an IMRT plan with 178 small fields. Therefore, the technique of using the VMAT model to predict IMRT plans does not impose any limitations on the dose distribution [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on statistical discrepancies, Batumalai V [ 5 ] observed that even the engagement of experienced plan developers does not necessarily guarantee the variations in plan quality. Wu Hao et al [ 13 ] also concluded that intensity-modulated planning using KBP, along with manual fine-tuning, was not only able to achieve a clinically acceptable level in almost all of the plans but also significantly reduced the planning time. This was based on a comparison of automated IMRT plans with conventional manual plans in 80 patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar strategies could be applied to CSI to minimize dose to adjacent OARs. Many studies have demonstrated the utilisation of avoidance sectors in VMAT planning to minimize radiation exposure to the OARs, a technique that could be adapted for the avoidance of critical structures in CSI as well [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge-based planning (KBP) is a type of radiotherapy planning which uses previously acquired knowledge of dose-volume histogram (DVH) parameters in relation to planning target volume and organ at risk locations to create a treatment plan, rather than relying solely on information from the current image used for dose calculation [13] . Several in-house models have been developed for multiple disease sites, with some models also being incorporated within commercial treatment planning software for several clinical scenarios [14] , [15] , [16] , [17] . These models employ geometrical features and the associated dosimetry of plans included in the model library to predict a range of achievable DVH for organs at risk (OAR) of new patients [18] .…”
Section: Introductionmentioning
confidence: 99%